Examining the spillover effects of problems at home on proactive customer service performance in the hospitality industry: the overlooked side of the work-family interface. Issue 3 (3rd April 2021) - Cheng, Bao; Guo, Gongxing; Dong, Yun; Peng, Yan
ABSTRACT: The present study explores the underlying mechanism of problems at home and proactive customer service performance (PCSP) in the hospitality industry. Integrating conservation of resources theory and boundary theory, it investigates the impact of hotel service employees' problems at home on PCSP as well as the mediating role of thriving at work and the moderating role of home–work segmentation preferences. We employed a three-wave survey and achieved 316 valid employee–supervisor dyads from five hotels in Guangdong Province in southern China. The results demonstrate that problems at home have a negative effect on PCSP and that thriving at work mediates this association. Furthermore, home–work segmentation preferences could weaken the effect of problems at home on thriving at work and the indirect effect of problems at home on PCSP via thriving at work.